Odpowiedzi

2010-01-18T13:54:29+01:00
A) = 39
b) = -50
c) = -2½
d) = 6,15
5 2 5
2010-01-18T13:58:44+01:00
A)11+(-12)+39+9-8=21
b)45+(-9)+(-91)+5=-50
c)-41/2+1/6+(-1/2)+1 1/3=-3 1/2
d)6.25+(-1/4)+(-3/5)+0.75=7 7/20
3 4 3
Najlepsza Odpowiedź!
2010-01-18T14:05:23+01:00
A) 11+ (-12) + 39 + 9 - 8 =11-12+39+9-8=39

b) 45 + ( -9) + (-91) +5 =45-9-91+5=50

c ) -4i1/2 + 1/6 + ( - 1/2 ) + 1i1/3 =-4i4/12+2/12-6/12+1i4/12=-6i6/12=-3i1/2

d) 6,25 + ( - 1/4) + ( - 3/5 ) + 0,75=6i5/20-5/20+12/20+15/20=6i27/20=7i7/20
7 4 7